INTERACTION SCHOOL FAMILY AND THE STUDY OF MATHEMATICS IN PEOPLE'S DAILY LIFE - Augusto, Emerson Aparecido (Revista Interface Tecnológica, 2023)
The school is a space where many people express their opinions and form their identity. The process of formation of a school takes place through the struggle for the rights of everyone who composes it. Educational institutions are made up of the surrounding community, and this integration between school, family and the study of mathematics in people's daily lives will define their identity, according to the culture and identity of each one. Community and family participation enters this context as an element of mediation between the school and the student, these being the main elements responsible for the student's education. The lack of participation often demonstrates the families' lack of interest in their children's education, and this responsibility cannot be left to the school or the teachers. But this participation mainly in the pedagogical process of the students in a process where the method of logical reasoning is used through financial and mathematical calculations, contributes to good results and the guarantee of education with more quality, also contributing to the better academic performance of the student and the best progress of the institution in the teaching process.
Keywords: School; Family; Interaction